PENGELOLAAN DANA INFAK UNTUK PENGEMBANGAN EKONOMI UMAT OLEH LEMBAGA AMIL ZAKAT, INFAQ, DAN SADAQOH NAHDATUL ULAMA (NU CARE-LAZISNU) NTB - Nurhalifah; Sofiana Wahyuningsih (Mudabbir: Jurnal Manajemen Dakwah, 2022)
Abstract: Management of infaq funds is one of the NU CARE-LAZISNU NTB programs in carrying out social functions. infaq funds originating from the people and managed productively for the economic development of the people. Economic constraints are the background for managing this infaq fund to help Mustahiq through KoinNU (infaq boxes) which are already scattered in various offices, homes and shops in West Nusa Tenggara and cooperate with Indomart Company in supporting the NU CARE-LAZISNU NTB program in the field of economic development through infaq funds. This form of implementation of infaq fund management provides assistance to people who have Micro, Small and Medium Enterprises (UMK) in the form of tools or goods needed to assist business production and open businesses to people who have potential or expertise by utilizing natural resources that exist around the environment. The results showed that (1) the management of infaq funds for the economic development of the people starting from planning carried out data collection of mustahiq who would receive assistance, organizing a special team to manage the infaq funds, implementation by distributing assistance to mustahiq in the form of tools and goods needed to develop businesses. and evaluation is done by controlling via cellular. (2) the obstacle in managing infaq funds for the economic development of the people is the lack of supervision of the beneficiaries because the distance and access to locations are limited so that they are not well controlled.